Towards Eco-Embodiment: Virtual Reality for Building Climate Change Awareness within Education for Sustainable Development - Kreimeier, Julian; Theelke, Luisa; Denzler, Jonathan; Enders, Florian; Kumar, Samarth; Roth, Daniel (2023 IEEE International Symposium on Mixed and Augmented Reality Adjunct (ISMAR-Adjunct), 2023)
To foster the understanding of the consequences of one's actions on climate change, low-threshold accessible and understandable content is needed. Virtual Reality (VR) has emerged as a valuable tool in the field of sustainable development education. However, there remains a lack of practical approaches and empirical insights into fostering climate change awareness through an eco-embodiment perspective. Our prototype addresses this gap by immersing users in a VR experience that simulates an everyday life scenario. The player's activities are calculated as if the entire population of Earth would exhibit such a behavior. At the end of the simulation, they are presented with the long-term scaled global consequences for the environment. Our preliminary evaluation demonstrates the effectiveness of this communication method but also reveals necessary gameplay optimizations toward longitudinal pre/post studies to quantify users' learning and behavioral changes.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Computing industry; Human computer interaction (HCI); Human-centered computing; Interaction paradigms; Professional topics; Social and professional topics; Sustainability; Virtual reality